A influência dos fatores psicossociais no curso da dor lombar, na performance física e na incapacidade em idosos comunitários: dados do estudo BACE - Renata Antunes Lopes (2015)
Introduction: Among the most prevalent painful conditions in the elderly is low back pain. Whereas pain and disability are multifactorial, it is known that psychosocial factors may be relevant to this context. However, these associations are still insufficiently understood, especially in elderly patients with worsened low back pain. Objective: To investigate psychosocial factors associations, check for cross associations between these factors, low back pain intensity, physical performance and self-reported disability and to understand the course of pain and psychosocial factors over 12 months and the longitudinal association among these variables in community-dwelling elderly with worsened back pain. Methods: We conducted three studies with Brazilian subsample (243 older patients, 68.26 ± 6.4 years) of international multicenter epidemiological study Back Complaints in the Elders -BACE. The instruments used were: Numeric Pain Rating Scale, McGill Pain Questionnaire, Catastrophizing Pain Scale, Center for Epidemiological Studies - Depression, Pain Locus of Control Scale (Form C), Tampa Scale for kinesiophobia, Roland Morris Disability Questionnaire and Short Physical Performance Battery. Descriptive analyzes to characterize the sample were conducted with centraltendency measures, variability and absolute and relative frequency. In studies 1 and 2 with cross-sectional design, multiple linear regression analyzes were conducted. In the first, the explanatory variables were kinesiophobia, locus of control (internal, at random, for health professionals and others) and depressive symptoms, being paincatastrophizing the outcome variable. In the second, the explanatory variables were kinesiophobia, locus of control (internal, at random, for health professionals and others), depressive symptoms and pain catastrophizing, being the outcome variables: pain intensity, physical performance and self-reported disability. In study 3, to determine the longitudinal association between psychosocial factors and painintensity, generalized estimating equations were used, considering as control variables: age, gender, education, pain frequency, previous treatments, regular physical activity and other pain complaints. Results: In the total sample, 92.7% were women, 57.6% had low education level and 39.5% were married. Most of the elderly (26.5%) reported pain all the time, and average intensity of the symptom of 4.44 ± 3.45. It was found association between catastrophizing pain and depressive symptoms, and this factor explained 48.3% of variance in pain catastrophizing. Inaddition, in cross examining, pain catastrophizing, locus of control in others and depressive symptoms explained 27.3% of the pain intensity variation, 17.5% of the physical performance variation and 42.3% of the self-reported disability variation. Longitudinally, pain reduction, catastrophizing and locus of control in medical and health professionals were found over the 12 month follow-up. Individuals who showed worsening in catastrophizing levels were twice as likely to also have a pain worsens in 12 month period and those who became more kinesiophobic had approximately 2.7 times greater chances to pain worsening during the same period. However, there was no causal association between any psychosocial factor variation in 6 months with the variation pain in 12 months, suggesting that these factors do nothave prognostic value. Conclusion: We found association between paincatastrophizing and depressive symptoms and between psychosocial factors and pain, physical performance and self-reported disability. Longitudinally, there was reduction in pain, pain catastrophizing and pain locus of control in health professionals over the 12 months of follow-up. Individuals who showed worsening in catastrophizing levels were pain worsens in 12 month period and those who became more kinesiophobic had approximately 2.7 times greater chances to pain worseningduring the same period.